The career meaning making of a single high school learner living with a sibling with a learning disorder – A Systems Theory Framework for career development - Alexander, Dinah; Dlamini, Nontobeko G (South African Journal of Higher Education, 2016)
This article explored the career meaning making of the participant and the perceived impact on his career trajectory caused by his living with a sibling with a learning disorder. The meaning making of this participant confirms previous research findings, namely that living with a sibling with a learning disorder propels the non-disabled sibling towards making certain holistic adjustments. In particular these adjustments have career-related implications as highlighted by the themes of responsibility towards the sibling, pressure to become independent and meaning making in a spiritual way. A qualitative, single case study approach was utilised. A postmodern approach towards career development within the framework of the Systems Theory was applied to explicate the career assessment and counselling of the participant living with a sibling with a learning disorder.